ANKLEBRACHIAL INDEX SEBAGAI PENANDA ATEROSKLEROSIS PADA NYERI PUNGGUNG BAWAH KRONIS - Trunojoyo Soeranggayoedha*, Salim Harris*, Manfaluthy Hakim*, Herqutanto** (NEURONA, 2010)
INTODUCTION CHRONIC LOW BACK PAIN LBP IS A PATOLOGIC CONDITION CAUSED BY LUMBAR DEGENERATION IT HAS BEEN PROVEN THAT ATHEROSCLEROSIS FACTORS BY ATHEROM PLAQUE FORMATION ON ABDOMINAL AORTIC WALL AND AA LUMBALISSACRALMEDIA STENOSIS HAS A ROLE IN THIS DEGENERATION PROCESS